Azerbaycan sessiz sinema dönemi - Balayeva, Narmin (My University, 2016)
Literatürde yedinci sanat olarak anılan sinema, Azerbaycan tarihinde her zaman önemli bir yere sahip olmuştur. İlk dönemlerinde anlık görüntü karelerinin bir araya gelmesi ile oluşan sinema zamanla müzik ve sesin de eklenmesiyle sürekli gelişmiştir. Bu çalışmanın konusu Azerbaycan’ın sessiz sinema dönemidir. Bu dönemin Azerbaycan'ın siyasi ve kültürel tarihine, aynı zamanda Azerbaycan sinema tarihine ışık tutması amaçlanmaktadır. Çar Rusyası döneminde çekilen az sayıdakı film Sovyetler zamanındakı örneklerden farklı olarak propaganda türünden uzaktır. Sovyet döneminde ağırlıklı olarak kadın özgürlüğü ve hurafeler konusunda filmler görülmeye başlamıştır. Aynı zamanda egemen ideolojiyi ve Sovyet dönemini öven eserlerin de olduğu görülmektedir. Azerbaycan sinemasındaki büyük değişim Sovyet döneminde görülmeye başlamıştır. Sovyet sineması öncelikle kitleleri eğitmeyi amaçlamış, genel ve siyasal bir eğitim sağlamanın yollarını arayarak kitlelerin düşün yapısıyla ilgili geniş bir propaganda çalışması yürütmüştür. Sovyetler birliğinde, Parti Komitesi’nin tanıtım kurulu tarafından yönetilen tüm sanat dalları bu amaçları izlemiştir. Sovyetler için sanat, salt bir sözcük olmaktan çok sosyalizm için verilen mücadelede ve sınıf çatışmasının ön saflarında kullanılan araçlardan biri olarak görülmüştür.

Cinema as one of the seven forms of fine arts has regularly had a prominent role and a fundamental position in the history of Azerbaijan. Its development process firstly made by gathering the momentary pictures together and later on by encompassing the music and sound in its formation and construction.The main topic of this research is the silent motion pictures period of Azerbaijan known as the silent cinema. This period has been regarded as an enlightenment of history, culture and the cinema history of Azerbaijan. The rare numbers of the movies made in the Russian kingdom era were conceptually totally different with the ones made in the Soviet Union of that period according to the propagandized issues. During the Soviet Union,Movies dominantly mentioning the freedom of women and superstitious matters in the society became to appear coming up by many movies which were made with the revolutionary spirits mostly in the favor of dominant ideology and praising The Soviet Union of that period. A revolutionary transformation became to exist after The Soviet Union period. The Soviet Union cinema had already aimed to educate different social categories. It has developed a vast propaganda in the social political construction while trying to finding the ways to establish its own general and political educational system. These politics had been inserted into all artistic fields during the Soviet Union period by the decision of the party committee at that times. Art beyond its literary meaning had been a tool in the challenge to carry on the socialism and a leading means during the social category conflicts of that timesfor the Soviet Union.
Keywords: Azerbaycan; Sessiz sinema; Sinema; Tarih